The heritabilities and genetic relationships of the components of yield in wheat - Eisenberg, B. E.(Benjamin Elieser) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1957.